2019
DOI: 10.1002/jbmr.3750
|View full text |Cite
|
Sign up to set email alerts
|

Women With Pregnancy and Lactation–Associated Osteoporosis (PLO) Have Low Bone Remodeling Rates at the Tissue Level

Abstract: Pregnancy and lactation–associated osteoporosis (PLO) is a rare, severe, early form of osteoporosis in which young women present with fractures, usually multiple vertebral fractures, during late pregnancy or lactation. In studies of idiopathic osteoporosis (IOP) in premenopausal women, we enrolled 78 women with low‐trauma fractures and 40 healthy controls, all with normal menses and no secondary cause of bone loss. In 15 of the affected women, the PLO subgroup, fractures had occurred during late pregnancy or l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 51 publications
1
29
0
Order By: Relevance
“…The latest and largest bone biopsy study in PLAO women where bone biopsies were performed 12 months postpartum, aimed to assess the baseline state of bone remodeling. Transiliac bone biopsies in these women, showed a low bone turnover state, which was also confirmed by circulating bone turnover markers compared to patients affected by idiopathic osteoporosis, itself already a state of low bone formation (97). This study showed a dissociation between low PINP in PLAO compared to controls, while the concentration of C-terminal telopeptide of type 1 collagen did not significantly differ (97).…”
Section: Pregnancy-and Lactation-associated Osteoporosissupporting
confidence: 69%
See 1 more Smart Citation
“…The latest and largest bone biopsy study in PLAO women where bone biopsies were performed 12 months postpartum, aimed to assess the baseline state of bone remodeling. Transiliac bone biopsies in these women, showed a low bone turnover state, which was also confirmed by circulating bone turnover markers compared to patients affected by idiopathic osteoporosis, itself already a state of low bone formation (97). This study showed a dissociation between low PINP in PLAO compared to controls, while the concentration of C-terminal telopeptide of type 1 collagen did not significantly differ (97).…”
Section: Pregnancy-and Lactation-associated Osteoporosissupporting
confidence: 69%
“…These novel findings suggest the possibility of an underlying defect in osteoblast function taking into consideration the lower bone formation reported in PLAO women in the absence of lower osteoblast number (97).…”
Section: Pregnancy-and Lactation-associated Osteoporosismentioning
confidence: 68%
“…Cohen et al evaluated a group of women with PLO and observed that they had lower tissue mineral apposition rates and bone formation rates assessed by transiliac bone biopsy in comparison with women with premenopausal osteoporosis. Based both on serum remodeling markers and micro-CT findings, they reported that women with PLO had evidence of low bone formation, in absence of lower osteoblast numbers, suggesting the possibility of an underlying defect in osteoblast function [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…These observations are in agreement with a previous study in which a slight increase in the concentration and activity of bone turnover markers (osteocalcin, alkaline phosphatase, C-telopeptide of type I collagen) associated with the presence and healing of fresh bone fractures were observed in some women with PLO [ 60 , 61 , 62 ]. Moreover, bone biopsies of some PLO patients have indicated increased resorption or decreased activity of osteoblasts [ 40 , 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%